Single-incision laparoscopic splenectomy in children with massive splenomegaly: A prospective, monocentric pilot study - Wang, Congjun; Su, Cheng; Chen, Chao; Tang, Xianming; Wang, Hong; Li, Wei; Li, Yanqiang; Liu, Qiang; Chen, Peng; Li, Yong; Luo, Yige (Frontiers in Pediatrics, 2023)
Background: Single-incision laparoscopic splenectomy (SILS) remains a challenging procedure because of the technical difficulty. In this prospective study, we aimed to evaluate the efficacy and safety of SILS in children with massive splenomegaly. Methods: Pediatric patients with massive splenomegaly were recruited for SILS in a university-affiliated hospital. The data on patient demographics, clinical features， operative variables, and perioperative outcomes were collected prospectively and analyzed. According to the different surgical instruments, the patients were randomly assigned into two groups: the SILS with straight surgical instrument (SILS-S) group and the SILS with curved surgical instrument (SILS-C) group. A two-group comparative analysis was conducted using perioperative data from the different surgical instrumentation systems. Results: A total of 120 patients were included, of which 103 patients (success group, 85.83%) had complete SILS, the other 17(failure group, 14.17%) patients were converted to open (n=4, 33.33%) or multi-incision laparoscopic surgery (n=13, 10.83%). The major cause for surgical failure is uncontrollable bleeding (n=14, 82.35 %), and age, height, and weight were the risk factors for failure of SILS, but none of the parameters were independent risk factors. The blood loss in the success group was less than that in the failure group, but no significant differences in other operative and outcome indicators. For SILS, the mean (±SD) operative time was 188 (±48.70) minutes, the median intraoperative blood loss (min, max) was 20 (5, 290) ml, the mean (±SD) time of first anal exhaust was 23.9 (±7.73) hours， and the mean (±SD) postoperative hospital stay was 4.72 (±1.03) days. The median pain score was 3 on 1 day, and 1 on 3 days after the operation. Postoperative complications were identified in 8 (7.77%) cases. However, there were no peri-operative deaths in this series. The SILS-C group had a significantly shorter operation time than the SILS-S group (mean ± SD, 172±44.21 vs 205 ±47.90 minutes). There were no significant differences between the two groups in other perioperative data (P < 0.05). Conclusions: SILS is a safe and feasible treatment in pediatric patients with massive splenomegaly, and curved surgical instrumentation has contributed to developing surgical manipulation.